1981
DOI: 10.1007/bf00609587
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and salivary pharmacokinetics of caffeine in man

Abstract: Plasma and salivary caffeine concentrations were measured by gas-liquid chromatography in 6 healthy caffeine-free volunteers following oral administration of 50, 300, 500 and 750 mg caffeine. Caffeine was also given to a single subject intravenously in doses of 300, 500 and 750 mg. Caffeine was rapidly absorbed and was completely available at all doses. The apparent first-order elimination rate constant decreased linearly with dose and was 0.163 +/- 0.081 h-1 for 50 mg and 0.098 +/- 0.027 h-1 for 750 mg. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
111
0
7

Year Published

1987
1987
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(130 citation statements)
references
References 22 publications
12
111
0
7
Order By: Relevance
“…The relative contribution of phase I CYP isoforms vs. phase II enzymes in the PBPK models of APAP and CAF was 70:30, and 100:0, respectively ( Figure 2). The established reference PBPK models were validated for additional doses and individual subgroups by using clinical PK data from different studies not used for developing the reference PBPK models 11, 22, 23, 24, 26, 27. Note that all model parameters were left unchanged in this validation step except study parameters specifying the design of the clinical trials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative contribution of phase I CYP isoforms vs. phase II enzymes in the PBPK models of APAP and CAF was 70:30, and 100:0, respectively ( Figure 2). The established reference PBPK models were validated for additional doses and individual subgroups by using clinical PK data from different studies not used for developing the reference PBPK models 11, 22, 23, 24, 26, 27. Note that all model parameters were left unchanged in this validation step except study parameters specifying the design of the clinical trials.…”
Section: Resultsmentioning
confidence: 99%
“…PD responses of CAF and APAP were therefore predicted for an in vivo situation by the application of PICD14 thereby coupling in vitro toxicity data with drug‐specific PBPK models. To validate the PBPK models, simulated drug concentrations of APAP, CAF, and their main metabolites (APAPC, acetaminophen cysteine; APAPG, acetaminophen glucuronide; APAPS, acetaminophen sulfate; PX, paraxanthine; TP, theophylline; and TB, theobromine) were first assessed with clinical PK profiles from several studies obtained for different dosage regimens 8, 11, 20, 21, 22, 23, 24, 25, 26, 27. Using an additive PD response model, the influence of CAF on APAP‐induced hepatotoxicity was analyzed for key cellular processes and individual genes.…”
Section: Figurementioning
confidence: 99%
“…Saliva sampling is considered a good method for frequent measurement of caffeine pharmacokinetics (Newton et al, 1981;Suzuki et al, 1989), with a linear relationship reported between caffeine concentrations in saliva and plasma, and salivary caffeine levels reported to be around 80% of plasma levels (Perera et al, 2011;Zylber--Katz et al, 1984). Collection, storage and analysis procedures are supplied as Supplementary Material.…”
Section: Salivary Caffeine Concentrationsmentioning
confidence: 99%
“…Cortisol is a stress hormone that has a major role in facilitating the fight or flight mechanism. Under stress, cortisol provides the body with glucose by utilizing protein stores via gluconeogenesis in the liver [20]. Elevated cortisol level consistently produces glucose leading to increased blood sugar levels along with insulin suppression which causes the cells to be starved of glucose [21].…”
Section: Discussionmentioning
confidence: 99%